Authenticity with a bang: Exploring suburban culture and migration through the new phenomenon of the Richmond Night Market. (February 2015) - Pottie-Sherman, Yolande; Hiebert, Daniel
This paper considers the suburban night through the recent cultural phenomenon of the Summer Night Market in Richmond, British Columbia, Canada. Night markets have existed in China since the 8th century, and have followed Chinese migration, first to Southeast Asia, and more recently, to Canada. Richmond, because of significant Asian settlement in the 1990s, is known as the 'new Chinatown' ethnoburb of Metro Vancouver. Its night market is a weekend evening event where predominantly Asian vendors sell clothing, food and a range of other products to the Chinese community and others attracted by the spectacle or seeking a bargain. The Richmond night-time landscape contrasts sharply with the 24/7 cultures of Hong Kong, Taiwan and Mainland China. But the Richmond market makes possible a cultural use of night-time space – for strolling and meeting at night – in a suburban landscape that is quiet after 18:00 h. In the last three years, the market has been re-branded as a multicultural, rather than Chinese, space. We explore the role of this market in the night-time leisure culture of Metro Vancouver, through themes of the changing nature of the suburbs, suburban night places, and the (messy) question of authenticity in an age (and place) of ongoing migration and super-diversity.